Measuring the Level of Entrepreneurial Orientation: Analytical Research in the National Security Advisory - Rasheed Yarallah, Muntaha; Jassim Mohammed, Nisreen (Journal of Economics and Administrative Sciences, 2024)
The current research aims to measure the level of entrepreneurial orientation and its dimensions (creativity, independence, proactivity, risk tolerance, and achievement) in the National Security Chancellery, as its importance and role in guiding senior leaders of the chancellery to make strategic decisions with high quality in various Iraqi concerns, more specifically the security aspect. The data was collected from 94 individuals (the research sample) from the research community (120) individuals at different administrative levels and intentionally where the questionnaire was adopted as a main tool for data collection and the primary data was analyzed through descriptive and inferential statistical methods (arithmetic mean, standard deviation, coefficient of variation, and relative importance) using the statistical analysis program (SPSS V28). The most prominent result was the direction of the National Security Chancellery to continuously improve its entrepreneurial orientation (creativity, proactivity, and taking risks). While independence and achievement came in the last order).